2022
DOI: 10.1590/2177-6709.27.6.e2221150.oar
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alpha binaural beat music on orthodontic pain after initial archwire placement: A randomized controlled trial

Abstract: Objective: The objective of this article was to evaluate the effect of alpha binaural beat music on pain level after initial placement of a maxillary fixed appliance, compared to music without binaural beats (placebo) and no music (control). Methods: 60 patients undergoing maxillary fixed orthodontic appliance and initial archwire placement were randomly allocated into the three aforementioned groups. The pain level experienced was monitored for the following seven days, using the short-form McGill pain quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This study also found a significant increase in the mean Numerical Rating Scale (NRS) score, indicating a decrease in headache intensity before and after listening to alpha binaural beats. This is consistent with a study by Alya et al in 2022 on 60 patients with orthodontic pain after archwire installation, where the sensory and psychological aspects of pain intensity significantly decreased in the binaural beat music (BBM) group compared to the control group, measured by the Visual Analog Scale (VAS) after the fifth day (Aly et al, 2023).…”
Section: Comparison Of Headache Numerical Rating Scale (Nrs) Scores B...supporting
confidence: 91%
“…This study also found a significant increase in the mean Numerical Rating Scale (NRS) score, indicating a decrease in headache intensity before and after listening to alpha binaural beats. This is consistent with a study by Alya et al in 2022 on 60 patients with orthodontic pain after archwire installation, where the sensory and psychological aspects of pain intensity significantly decreased in the binaural beat music (BBM) group compared to the control group, measured by the Visual Analog Scale (VAS) after the fifth day (Aly et al, 2023).…”
Section: Comparison Of Headache Numerical Rating Scale (Nrs) Scores B...supporting
confidence: 91%
“…To improve patients' quality of life, several strategies can be implemented. Orthodontic pain can be managed through various methods, including medication, 49 mechanical therapies, 50 behavioral interventions such as cognitive-behavioral therapy (CBT), 51 music 52 and exercise. 53 Combining these approaches, especially during the initial phases of orthodontic treatment when pain is most pronounced, can alleviate patients' discomfort and help them adapt more comfortably to their orthodontic appliances.…”
mentioning
confidence: 99%